The Effect Of Reparameterisation On The Behaviour Of Nonlinear Estimates - Mohamed Ramli, Norazan (2000)
This thesis discussed nonlinear modeling and measures of nonlinear behaviour. A set of data, representing the average weight of dried tobacco leaves (in Several nonlinear models were used to fit the data, however only the Gompertz and the Logistic models were found to be suitable. The estimates of the para meters were calculated by using the Gauss-Newton algorithm in SPLUS Programming Language. A good estimator was the one which had the proper ties closed to the behaviour of a linear estimate . The non linear behaviour of the estimates was assessed using two different approaches , namely the analytical and the empirical approaches . These approaches were employed so that they could complement the existence of any laggings.